The long polar fimbriae (lpf) operon and its flanking regions in atypical bovine Escherichia coli O157:H43 and STEC O136:H12 strains - Sváb, Domonkos (2013)
Long polar fimbriae (Lpf) are intestinal adhesins and important virulence factors of pathogenic Escherichia coli strains. We cloned and sequenced the lpf2-1 operon (lpf2ABCD) and its flanking regions of an intimin- and Shiga toxin-negative E. coli O157:H43 strain of bovine origin, and also sequenced the lpf2-1 operon of 6 additional atypical O157 bovine Escherichia coli strains of various serotypes. Nucleotide sequence comparison of these lpf operons showed sequence conservation as they contained only four polymorphic nucleotide positions. Investigation of these O157 strains as well as 13 Escherichia coli Reference Collection (ECOR) strains carrying the lpf2-1 allele revealed high degree of sequence conservation in the lpf2 flanking regions. The lpf2-1 allele is also present in a bovine Shiga toxin-producing E. coli STEC O136:H12 strain and in vitro adherence assays revealed that the absence of lpf2-1 in this strain did not affect its host cell-binding properties. Our data indicate that lpf2 loci is highly conserved in E. coli isolates, however, its role in adherence might be masked by other uncharacterized adhesins.